Phenylethanoid Glycoside-Enriched Extract Prepared from Clerodendrum chinense Leaf Inhibits A549 Lung Cancer Cell Migration and Apoptosis Induction through Enhancing ROS Production - Chuda Chittasupho; Sirivan Athikomkulchai; Weerasak Samee; Mingkwan Na Takuathung; Wipawadee Yooin; Kasirawat Sawangrat; Chalermpong Saenjum (Antioxidants, 2023)
This study aims to investigate the antioxidant and anti-cancer activities of Clerodendrum chinense leaf ethanolic extract. The phenylethanoid glycoside-enriched extract, namely verbascoside and isoverbascoside, was determined in the ethanolic C. chinense leaf extract using the validated HPLC method. The ethanolic extract showed DPPH and ABTS free radical scavenging activities with the IC50 values of 334.2 ± 45.48 μg/mL and 1012.77 ± 61.86 µg/mL, respectively, and a FRAP value of 88.73 ± 4.59 to 2480.81 ± 0.00 µM. C. chinense leaf extract exhibited anti-proliferative activity against A549 lung cancer cells in a dose- and time-dependent manner, with the IC50 value of 340.63 ± 89.43, 210.60 ± 81.74, and 107.08 ± 28.90 µg/mL after treatment for 24, 48, and 72 h, respectively. The IC50 values of verbascoside, isoverbascoside, and hispidulin were 248.40 ± 15.82, 393.10 ± 15.27, and 3.86 ± 0.87 µg/mL, respectively, indicating that the anti-proliferative effects of the C. chinense leaf extract mainly resulted from hispidulin and verbascoside. The selectivity index (SI) of C. chinense leaf extract against A549 lung cancer cells vs. normal keratinocytes were 2.4 and 2.8 after incubation for 24 and 48 h, respectively, suggesting the cytotoxic selectivity of the extract toward the cancer cell line. Additionally, the C. chinense leaf extract at 250 µg/mL induced late apoptotic cells up to 21.67% with enhancing reactive oxygen species (ROS) induction. Furthermore, the lung cancer cell colony formation was significantly inhibited after being treated with C. chinense leaf extract in a dose-dependent manner. The C. chinense leaf extract at 250 µg/mL has also shown to significantly inhibit cancer cell migration compared with the untreated group. The obtained results provide evidence of the anti-lung cancer potentials of the C. chinense leaf ethanolic extract.